Myrmecodia pendens Bulb Extract in the Lele Dumbo (Clarias gariepinus) Feed: Effects on the Growth Performance, Survival, and Blood Indices - Rudy Agung Nugroho; Retno Aryani; Hetty Manurung; Yanti Puspita Sari; Rudianto Rudianto (Department of Aquaculture, 2022)
This feeding experiment was performed to determine the effects of Myrmecodia pendens bulb extract (MBE) supplementation in fish feed on the growth, survival, and hemato-biochemical profile of Clarias gariepinus. A group of fish was fed with 0.25; 0.50; 1.0; 2.0% MBE and compared to control group (without MBE) for 75 days observation. At the end of feeding trial, growth parameters, hematological profile such as red blood cells (RBC), white blood cells (WBC), Hemoglobin (Hb), Hematocrit (Htc), differential leukocyte, blood plasma biochemistry (glucose, total albumin, cholesterol, and triglyceride), the hepatosomatic (HSI) and intestinal somatic index (ISI) were measured. Survival of all fish was also counted every two weeks. Supplementation MBE above 0.25% resulted significantly higher final biomass weight (FBW), body weight gain (BWG), daily weight gain (DWG), and average weekly gain (AWG). Meanwhile, fish group fed dietary MBE above 1.0% had significantly higher specific growth rate (SGR) (3.32±0.15) than other groups. Fish fed 1.0% of MBE also showed better value of feed conversion ratio (FCR) (1.13±0.03), Hb, and HSI compared to others group. Survival, neutrophil, monocyte, and ISI of all groups was not affected by any concentration of MBE supplementation. Dietary MBE above 0.5% enhanced RBC, WBC, Hematocrit, platelet (PLT), lymphocyte, blood plasma biochemistry such as glucose, total albumin, and triglyceride. Cholesterol of fish fed MBE in the diet showed incrementally enhanced. Present finding suggested that 1.0% MBE in the diet of Clarias gariepinus is recommended to enhance growth, survival, and blood profiles